2017
DOI: 10.4194/1303-2712-v17_5_11
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to establish causes of variation in body weight of Atlantic sturgeons reared for reintroduction program. Substantial disproportion of individuals released into freshwaters may influence reintroduction success. Histological analysis of white muscle was conducted due to large share of this tissue in body weight. Comparison of morphological structure of white muscle tissue showed significant statistical differences between the fast and the slow growing sturgeons. Mosaic hyperplasia (MH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The present study showed differences in the diameters of red muscle fibers in different regions in the two species and a decrease in diameters of the red muscle fibers in the posterior region (caudal peduncle) which represents a muscle growth and development in the fish by the two processes; hyperplasia and hypertrophy (Adamek et al, 2017). The increase of the numbers of muscle fibers in the posterior region of the fish reflects the importance of this region in fish locomotion (Al-Badri, 1985;Mansour, 1998Mansour, , 2005.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The present study showed differences in the diameters of red muscle fibers in different regions in the two species and a decrease in diameters of the red muscle fibers in the posterior region (caudal peduncle) which represents a muscle growth and development in the fish by the two processes; hyperplasia and hypertrophy (Adamek et al, 2017). The increase of the numbers of muscle fibers in the posterior region of the fish reflects the importance of this region in fish locomotion (Al-Badri, 1985;Mansour, 1998Mansour, , 2005.…”
Section: Discussionmentioning
confidence: 48%
“…The muscular tissue constitute up to 60-80 % of the fish body weight. The fish swim using a combination of paired, unpaired fins and undulations of the myotomal muscles (Johnston, 1981;Altringham and Ellerby, 1999;Adamek et al, 2017). Red muscle fibers usually constitute less than 10 % of the myotomal musculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation